Utilization of Facebook Live Streaming in Online Missionary Endeavor at the Ar-Risalah Al-Khairiyah Foundation - Suhendri suhendri; Hasan Hamzah Lubis; Dasa Syawal Syahputra; Taufik Hidayat (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
Today's social media is experiencing a very big development. Many social media platforms are competing to present the latest features to attract the interest of netizens or users. One of the large and widely used social media platforms in Indonesia is Facebook. Since 2015, Facebook has officially added live streaming features to its applications, both for Android, iOS and PC applications. The emergence of the Facebook live streaming feature is in great demand by content creators, gamers, academics and also preachers both individually and in institutions. The Arrisalah Alkhairiyah Foundation is a social, educational and da'wah foundation that has a da'wah office that oversees the Isyraf Dakwi division. Various da'wah programs carried out by the Isyraf Dakwi division, one of which is conducting a live streaming study using social media Facebook. This study uses a qualitative descriptive method, the purpose of which is to describe the use of Facebook live streaming social media for online da'wah activities. The research findings, it was found that the use of Facebook live streaming was initially an alternative da'wah program which was stopped due to the covid 19 pandemic. The advantages of the program through this live streaming are that it is cost and time efficient and is easily accessible to viewers and the study materials are kept stored. The obstacles encountered in live streaming are the poor internet connection and the lack of promotion of Isyraf Dakwi's account channel so that the number of viewers tends to tend to